ANALISIS PENGARUH PEMASARAN MEDIA SOSIAL INSTAGRAM, PERSEPSI BIAYA PENDIDIKAN DAN BRAND RECOGNITION TERHADAP KEPUTUSAN PEMBELIAN PADA STIE WIYATAMANDALA - Sutrisno Sutrisno (STIE Wiyatamandala, 2020)
The increasing complexity of competition has made business actors including STIE Wiyatamandala more able to survive and continue to grow. Therefore, it is necessary to analyze the variables that are relevant to student decisions in choosing STIE Wiyatamandala. This research was conducted with the aim of analyzing the effect of social media instagram, perception of education cost, and brand recognition on student purchasing decisions. From the results of the analysis, it was found that the variables of Instagram social media marketing, price perception, and brand recognition had a significant positive effect on purchasing decisions, and price perception was considered the variable that had the most positive influence on purchasing decisions. These population data were collected from Wiyatamandala students batch 2016 - 2019, with number of samples of 61 people respondents. The sample was chosen by using purposive sampling technique. Primary data were collected by using questionnaire method and analyzed by SPSS using multiple linear regression analysis Based on the research results, it was found that the variables of social media instagram (X1), perception of education cost (X2), and brand recognition (X3) had a significant positive effect on purchasing decisions (Y). The perception of education cost is considered to be the variable with the most positive influence on purchasing decisions